1997
DOI: 10.2172/481880
|View full text |Cite
|
Sign up to set email alerts
|

Integrated thermal and nonthermal treatment technology and subsystem cost sensitivity analysis

Abstract: This report was prepared as a n account of work spomored by a n agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, make any warranty, express or implied, or assumes any legal liability or mpomibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disdosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cost analysis has been treated extensively elsewhere (Shropshire et al 1995;Harvego and Schafer 1996), and has shown that overall life-cycle costs are most affected by disposal costs. This conclusion emphasizes the volume reduction capabilities of candidate waste forms and associated processes.…”
Section: Waste Mass Fractionmentioning
confidence: 99%
“…Cost analysis has been treated extensively elsewhere (Shropshire et al 1995;Harvego and Schafer 1996), and has shown that overall life-cycle costs are most affected by disposal costs. This conclusion emphasizes the volume reduction capabilities of candidate waste forms and associated processes.…”
Section: Waste Mass Fractionmentioning
confidence: 99%